Tomatidine relieves neuronal damage in spinal cord injury by inhibiting the inflammatory responses and apoptosis through blocking the NF-κB/CXCL10 pathway activation - Wang, Xu; Huang, Wei; Sun, Hao; Wang, Hua; Wang, Dongxu; Wang, Yongxiang (Frontiers in Pharmacology, 2024)
Background Spinal cord injury (SCI) is a neurological disease characterized by high disability and mortality rates. Tomatidine, a natural steroid alkaloid, has been evidenced to have neuroprotective properties. However, the underlying mechanisms of tomatidine in treating SCI remain ambiguous. This study aimed to illustrate the molecular mechanisms of tomatidine in modulating the inflammatory response and promoting functional rehabilitation after SCI. Methods Sprague–Dawley (SD) rats were used to construct an in vivo SCI model and were intraperitoneally injected with tomatidine (5, 10, or 20 mg/kg) for 7 days, followed by treatment with the nuclear factor-κB (NF-κB) pathway agonist (PMA). In addition, lipopolysaccharide (LPS)-induced PC-12 cells were used to establish an SCI cell model and were stimulated with tomatidine, PMA, or a CXCL10 inhibitor. The pathophysiological changes and neurological function were evaluated using blood-brain barrier (BBB) scoring, water content determination, hematoxylin and eosin (H&E) staining, and TUNEL assay. Levels of inflammatory cytokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6, were measured. Cell proliferation, apoptosis, and the expression of C-X-C motif chemokine ligand 10 (CXCL10) were determined. Moreover, the expression of cleaved-caspase 3, caspase 3, CXCL10, p-p65, and p65 were analyzed. Results Our data revealed that tomatidine promoted neuronal damage recovery, reduced histopathological changes, elevated cell proliferation, and inhibited the apoptosis and inflammatory factor levels in spinal cord tissues and LPS-induced PC-12 cells. Moreover, tomatidine decreased the expression of CXCL10 in vitro and in vivo, which was accompanied by the regulation of the NF-κB pathway. However, the NF-κB pathway agonist PMA reversed the protective effect of tomatidine in vitro. PMA also enhanced the CXCL10 expression and stimulated the activation of the NF-κB pathway, as demonstrated by the upregulation of phosphorylated p65. The CXCL10 inhibitor had effects similar to tomatidine on cleaved-caspase 3 expression, CXCL10 expression, and the NF-κB pathway. Conclusion Tomatidine can alleviate neuronal damage in SCI by inhibiting apoptosis and inflammation through the NF-κB/CXCL10 pathway. Our findings provide a novel therapeutic target and candidate for the treatment of SCI.